Factors affecting the intention of the rice farmers to adopt the integrated cash waqf environmental protection model: an empirical study in Kedah Malaysia - Rafia, Afroz; Muhibbullah, Md.; Morshed, Niaz (Korea Distribution Science Association, 2019)
The objectives of this study are to propose the Integrated Waqf Environmental Protection Model (IWEP) and investigate the farmers’ intention to adopt it. In developing the IWEP model and investigating farmers’ willingness to adopt it, this study surveyed 4 00 farmers in Kedah. The intention of the farmers to adopt the proposed model was analysed by adding perceived barriers and socio socio-economic variables into the theory of reasoned action (TRA) model. The collected data were processed using structural equatio equation modeling (SEM). The SEM results show that the subjective norm is positive and has a significant impact on the intenti ons of low low-income farmers to accept the IWEP model. This indicates that the decision of the low low-income farmers to accept the IWEP model is significantly influenced by their family members, neighbours and friends. Furthermore, awareness and perceived barriers have a greater impact on the elderly, highly educated and wealthy farmers. The findings indicate that the elderly, highly educated and wealthy farmers are aware of climate change and they perceive higher risks or barriers to climate change. As a result, they are more likely to have an adaptation intention. If we encourage people to create a waqf fund, we can increase the value of the farmer and the country’s total GDP.